Ways of solving problems of graduates on the labour market: interaction of educational institutions and employers - Polishchuk, О. А. (Видавництво Львівської політехніки, 2014)
The necessity of interaction between educational institutions and employers at the present stage of labor market development is substantiated. There is presented the scheme which describes advantages of such interaction for both educational institutions and employers. The scheme is directed at establishing mutually beneficial cooperation between them. The main approaches the effective application of which will allow to solve positively a complex of the problem issues connected with employment, improvement of professional quality and the number of graduates on the labor market in Ukraine are offered. Обґрунтовано необхідність взаємодії навчальних закладів та працедавців на сучасному етапі розвитку ринку праці. Представлено схему, яка описує переваги як для навчальних закладів, так й для працедавців, та скерована на встановлення взаємовигідної співпраці між ними. Запропоновано основні підходи, ефективна реалізація яких дасть змогу позитивно вирішувати комплекс проблемних питань, пов’язаних з працевлаштуванням, професійним становленням та зростанням випускників на ринку праці України.
Засоби вирішення проблем випускників на ринку праці: взаємодія навчальних закладів і працедавців
Keywords: labor market; graduate; employment; educational institution; employer; ринок праці; випускник; працевлаштування; навчальний заклад; працедавець